2001
DOI: 10.1063/1.1335828
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of wet oxidation of silicon based on the interfacial silicon emission model and comparison with dry oxidation

Abstract: Silicon oxidation in wet ambients is simulated based on the interfacial silicon emission model and is compared with dry oxidation in terms of the silicon-atom emission. The silicon emission model enables the simulation of wet oxidation to be done using the oxidant self-diffusivity in the oxide with a single activation energy. The amount of silicon emission from the interface during wet oxidation is smaller than that during dry oxidation. The small emission rate for wet oxidation is responsible for the insignif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 24 publications
2
84
0
Order By: Relevance
“…7 Apart from these features ͑initial oxidation enhancement in O 2 but not in H 2 O, sublinear dependence on P O 2 , dependence on substrate orientation͒ already highlighted by Uematsu et al, we have identified additional experimental results that can be qualitatively explained by the interfacial emission model. These are the experiments showing an enhancement of the oxidation after annealing of thin oxides in inert atmosphere.…”
Section: ͑6͒supporting
confidence: 54%
See 4 more Smart Citations
“…7 Apart from these features ͑initial oxidation enhancement in O 2 but not in H 2 O, sublinear dependence on P O 2 , dependence on substrate orientation͒ already highlighted by Uematsu et al, we have identified additional experimental results that can be qualitatively explained by the interfacial emission model. These are the experiments showing an enhancement of the oxidation after annealing of thin oxides in inert atmosphere.…”
Section: ͑6͒supporting
confidence: 54%
“…Uematsu et al have succeeded in fitting several series of X͑t͒ curves with very good accuracy: Series 1, dry oxidation of Si͑100͒ at 1 atm measured by several authors in the 800− 1200°C temperature range, 6,7 notably the experimental points by Massoud et al 8 in the thin oxide regime; Series 2, the oxygen pressure dependence in the 1-20 atm range and thickness above 100 Å ͑Refs. 7 and 9͒ measured by Lie et al; 10 Series 3, dependence on Si substrate orientations ͑100͒ and ͑111͒ at several temperatures and oxygen pressures 11 measured by Massoud et al 8 and Lie et al; 10 and Series 4, a similar series for wet oxidation.…”
Section: ͑6͒mentioning
confidence: 99%
See 3 more Smart Citations